Implementation of Electronic Traffic Law Enforcement by the Riau Islands Regional Police to Improve Traffic Law Awareness in Batam City - Akbar, Muhammad Dzaky; Tan, Winsherly; Nurlaily, Nurlaily (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: Road users' legal awareness of the road itself is a key factor driving the urgency of creating safety and order on the roads. In Batam City, the Riau Islands Regional Police's (Polda Kepulauan riau) implementation of Electronic Traffic Law Enforcement (ETLE) is a means of enforcing traffic laws to increase public awareness and compliance with traffic laws through an electronic ticketing system based on Closed-Circuit Television (CCTV).Purposes of the Research: This research analyzes the implementation of ETLE in Batam City and its effectiveness in terms of increasing legal awareness of drivers, especially in Batam City, as well as various obstacles faced in the implementation of ETLE itself, both problems from the community and problems with law enforcement officers who organize ETLE.Methods of the Research: This research is an empirical legal study. The approaches used in this study are the statute approach and the sociological approach. The statute approach is used to examine the legal basis for implementing ETLE. Meanwhile, the sociological approach is used to understand how the law is applied in practice by the police. The data collection method for this research is through interviews with law enforcement officers, field observations, and analysis of secondary data from related sources.Results Main Findings of the Research: The final results of this research found that the implementation of ETLE implemented by the Riau Islands Regional Police (Polda Kepulauan Riau) in Batam City continues to face significant challenges and has not yet operated effectively. Although ETLE has recorded more than 1.526.013 traffic violations since its implementation, the extremely low rate of ticket resolution only approximately 13.232 offenders fulfilling their legal obligations. One of the main obstacles is inaccurate vehicle ownership data, particularly in cases where vehicles have changed ownership but the name transfer process has not been completed, resulting in violation confirmation letters failing to reach the actual offenders. Furthermore, the very limited number of static ETLE cameras restricts the scope of surveillance and causes many traffic violations to go unrecorded by the system.